If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-(X-1)=2
We move all terms to the left:
X-(X-1)-(2)=0
We get rid of parentheses
X-X+1-2=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| 3y-8/4+6=4 | | X-x-1=2 | | 4(x-4)=5(x-1) | | 3(x-5=9 | | 2x+10=−15 | | 2×+y=340 | | 3x-25=85 | | 12x-2=11x+9 | | 3x-2(-4)=17 | | x—2=-14 | | 2x+4=4+x | | x+0.5=3.7 | | 4.9=v/5 | | v-9+17=56 | | 18+z=25 | | 3(3x-2)+7=40 | | c+2.9=-5.8 | | 41=4-6+m+13-7 | | 2/3x+6=x1/2+x1/4 | | 11=-x/7 | | 37=5-2+u-15 | | 2x^2-7x-12=10 | | 2+2x=92 | | 75+3x-15=180 | | 180=(15y-4)+(12y-5) | | 12/7x+3x=−24+3/7 | | 12=4x+4* | | 2x/5+5=-5 | | 127x+3x=−24+37 | | -2(2-x)+3x=-2(x-1) | | 8x-3•(x-4)=18 | | 5x+2-3(4)=5 |